The Effect of Individual Time Preferences on Smoking Behavior: Insights from Behavioral Economics - Moslem SOOFI; Ali AKBARI SARI; Farid NAJAFI (Tehran University of Medical Sciences, 2020)
Background: We aimed to explore the correlation between the time and risk preferences and the smoking behavior of adult population in western Iran. Methods: Overall, 792 individuals with the age of 35 to 65 yr participating in an ongoing national cohort study (Persian Cohort) were approached to complete a pre-structured questionnaire in 2017. Time preferences were measured using a standard choice-based method. The individuals' discount rates were identified by questions that offered binary monetary choices on immediate future and distant future, by making trade-offs between them. Probit regression model was used to investigate the relationship between time preferences and smoking when controlling for demographic and socioeconomic variables. Results: Time and risk preferences had statistically significant direct correlations with smoking. A unit increase in discount rate was associated with a 4.4% percentage point increase in the likelihood of being smoker. A present-biased individual had 5.7% percentage points lower likelihood of being smoker. Moreover, a unit increase in willingness to take the risk increased the likelihood of being a smoker by 1.5% percentage points. Conclusion: Time and risk preferences are important determinants of smoking behavior. These factors should be considered in designing effective prevention and control programs. Policies that increase the immediate costs of cigarette smoking or the immediate benefits of smoking cessation are likely to have a greater impact on reducing the prevalence of cigarette smoking.